2022
DOI: 10.3390/ph15020205
|View full text |Cite
|
Sign up to set email alerts
|

Magnolol and Luteolin Inhibition of α-Glucosidase Activity: Kinetics and Type of Interaction Detected by In Vitro and In Silico Studies

Abstract: Magnolol and luteolin are two natural compounds recognized in several medicinal plants widely used in traditional medicine, including type 2 diabetes mellitus. This research aimed to determine the inhibitory activity of magnolol and luteolin on α-glucosidase activity. Their biological profile was studied by multispectroscopic methods along with inhibitory kinetic analysis and computational experiments. Magnolol and luteolin decreased the enzymatic activity in a concentration-dependent manner. With 0.075 µM α-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…To study the type of interaction between α–glucosidase and baicalein, the plot of enzyme activity ( v ) versus α–glucosidase enzyme concentration was obtained ( Figure 7 C), suggesting a concentration–dependent reversible interaction since all straight lines obtained at different concentrations of baicalein pass through the origin of the axes, and their slope decreased with increasing concentrations of the inhibitor. Previous research showed similar behavior for other natural compounds, for example, luteolin, morin, magnolol, and α–mangostin [ 48 , 50 , 51 , 52 ]. Furthermore, the type of baicalein inhibition was also estimated with Michaelis–Menten and Lineweaver–Burk plots ( Figure 8 A,B) obtained using different substrate concentrations (0.5, 1.0, 1.5 and 2.0 mM p NPG), while maintaining constant enzyme concentration (0.05 µM).…”
Section: Resultsmentioning
confidence: 57%
“…To study the type of interaction between α–glucosidase and baicalein, the plot of enzyme activity ( v ) versus α–glucosidase enzyme concentration was obtained ( Figure 7 C), suggesting a concentration–dependent reversible interaction since all straight lines obtained at different concentrations of baicalein pass through the origin of the axes, and their slope decreased with increasing concentrations of the inhibitor. Previous research showed similar behavior for other natural compounds, for example, luteolin, morin, magnolol, and α–mangostin [ 48 , 50 , 51 , 52 ]. Furthermore, the type of baicalein inhibition was also estimated with Michaelis–Menten and Lineweaver–Burk plots ( Figure 8 A,B) obtained using different substrate concentrations (0.5, 1.0, 1.5 and 2.0 mM p NPG), while maintaining constant enzyme concentration (0.05 µM).…”
Section: Resultsmentioning
confidence: 57%
“…It was found to contribute to the effect of alpha-glucosidase inhibitory activity [ 13 ], but to date, there are still no reports on luteolin in G. amygdalinum ’s inhibitory effect against alpha-glucosidase. A previous report showed that luteolin has a non-competitive inhibition mechanism type [ 24 ]. Luteolin can also be found in Vernonia cinera , but its bioactivity is shown to be anti-inflammatory [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…83 although chalconaringenin could not achieve a specific IC50 value toward α-amylase even at the concentration of 100 µM, the introduction of either prenyl or geranyl substituent significantly increased the inhibitory activity of this compound indicating the importance of these groups toward the inhibition manner of this chalcones. Moreover, his study also showed that the introduction of the geranyl group (131) increased the inhibitory potency by 20 times and 4 times, compared with desmethylxanthohumol (123), against α-glucosidase and α-amylase, respectively. As an effort to evaluate the anti-diabetic activities of the chalcone derivatives, 28 chalcones and 13 chalcone analogues have been synthesized and assessed for their IC50 value toward the two enzymes by Rocha et al (2019).…”
Section: Chalconesmentioning
confidence: 98%
“…Luteolin (30) exhibits a similar inhibition profile on both enzymes but to a lesser extent of consent on αglucosidase. 15 out of 25 recorded findings 69,111,112,114,117,118,120,123,124,[127][128][129][130][131][132] showed stronger activity on α-glucosidase than acarbose, in contrast with the remaining 10 studies, 39,57,58,79,116,[133][134][135][136] making a 6:4 conflict. There was greater unity in the results of α-amylase inhibition, 39,137,138 confirming a moderate but generally weaker activity than acarbose on α-amylase (IC50 ranging from 14.57 µM to 1 mM).…”
Section: Flavonesmentioning
confidence: 99%